Modulating effects of heat-killed and live Limosilactobacillus reuteri PSC102 on the immune response and gut microbiota of cyclophosphamide-treated rats - Md. Sekendar Ali; Eon-Bee Lee; Yixian Quah; Syed Al Jawad Sayem; Muhammad Aleem Abbas; Kyoungho Suk; Seung-Jin Lee; Seung-Chun Park (Veterinary Quarterly)
In the present study, we investigated the potential immunomodulatory effects of heat-killed (hLR) and live Limosilactobacillus reuteri PSC102 (LR; formerly Lactobacillus reuteri PSC102) in RAW264.7 macrophage cells and Sprague–Dawley rats. RAW264.7 murine macrophage cells were stimulated with hLR and LR for 24 h. Cyclophosphamide (CTX)-induced immunosuppressed Sprague–Dawley rats were orally administered with three doses of hLR (L-Low, M-Medium, and H-High) and LR for 3 weeks. The phagocytic capacity, production of nitric oxide (NO), and expression of cytokines in RAW264.7 cells were measured, and the different parameters of immunity in rats were determined. hLR and LR treatments promoted phagocytic activity and induced the production of NO and the expression of iNOS, TNF-α, IL-1β, IL-6, and Cox-2 in macrophage cells. In the in vivo experiment, hLR and LR treatments significantly increased the immune organ indices, alleviated the spleen injury, and ameliorated the number of white blood cells, granulocytes, lymphocytes, and mid-range absolute counts in immunosuppressive rats. hLR and LR increased neutrophil migration and phagocytosis, splenocyte proliferation, and T lymphocyte subsets (CD4+, CD8+, CD45RA+, and CD28+). The levels of immune factors (IL-2, IL-4, IL-6, IL-10, IL-12A, TNF-α, and IFN-γ) in the hLR and LR groups were upregulated compared with those in the CTX-treatment group. hLR and LR treatments could also modulate the gut microbiota composition, thereby increasing the relative abundance of Bacteroidetes and Firmicutes but decreasing the level of Proteobacteria. hLR and LR protected against CTX-induced adverse reactions by modulating the immune response and gut microbiota composition. Therefore, they could be used as potential immunomodulatory agents.